The Role of Mechanical Mixing and Biologically Active Additives in Enhancing Cutlet Quality - Tetiana Prylipko; Tetiana Koval; Volodymyr Kostash; Volodymyr Tkachuk; Vita Kostash (Qubahan Academic Journal)
The research relevance is determined by the need to understand the effect of mechanical mixing and the use of biologically active additives on the quality of cutlet mass, which will optimize food technologies and create products with improved texture and nutritional value. This need stems from the fact that the quality and characteristics of culinary products are important criteria for consumers. The research aims to investigate the relationship between mechanical mixing parameters and the use of biologically active additives with structural and mechanical quality parameters of cutlet mass, to improve production processes and develop higher quality food products. Analytical methods, classification methods, functional methods, statistical methods, and synthesis methods were used to determine the quality of the cutlet mass. In the course of the study, a comprehensive analysis of the effect of various parameters of mechanical mixing and the use of various biologically active additives on the structural and mechanical characteristics of the cutlet mass was carried out. It was found that optimal mixing conditions and types of additional components can significantly improve the textural properties of the product. It was found that the use of certain biologically active additives helps to increase the resistance of the mass to mechanical stress and preserve its juiciness. These conclusions allow us to develop more effective strategies for the production of cutlet mass with improved quality and nutritional value. The practical significance of this study is to provide scientifically based recommendations for optimizing food production processes aimed at improving the quality and nutritional value of cutlet mass by studying the effect of mechanical mixing and biologically active additives on its structural and mechanical properties.